А.С.Пушкиний бүтээлийн монгол орчуулгын тойм: Mongolian translation review on literature proses of Pushkin.A.S - B., Demberelmaa; Ts., Tsogzolmaa (Mongolian Journal of Foreign Languages and Cultures, 2023)
This study presents an analysis carried on Mongolian translation of literary prose works of Alexander Sergeyevich Pushkin, a representative of the golden age of Russian literature. Over 330 literary works of Pushkin.A.S, a Russian great poet, have been translated into Mongolian language since 1936. Over the period 1921-1960, his 14 narrative poems, 5 fairy tales, 7 novel-in-verse, over 40 poems and during 1985-2005 over 200 poems were translated into Mongolian language. Prose works of great poet were initially translated by Mongolian great writers such as Natsagdorj.D, Damdinsuren.Ts, Chimed.Ch, Tsedenjav.Ts, Oyun.E and Perlee.Kh. Moreover, many Mongolian translators, such as Dondog Sonom, Magsar.Ts, Gun-Uils.D, and Dondog.Kh have made their precious contribution to the translation of Puskin poems into Mongolian language for the past 30 years.